Optimal Adjuvant Treatment Approach After Upfront Resection of Pancreatic Cancer: Revisiting the Role of Radiation Based on Pathologic Features. Issue 6 (December 2021) - Moaven, Omeed; Clark, Clancy J.; Russell, Gregory B.; Votanopoulos, Konstantinos I.; Howerton, Russell; Levine, Edward A.; Shen, Perry
Abstract : Objective: To identify the survival benefit of different adjuvant approaches and factors influencing their efficacy after upfront resection of pancreatic ductal adenocarcinoma (PDAC). Summary Background Data: The optimal adjuvant approach for PDAC remains controversial. Methods: Patients from the National Cancer Database who underwent upfront PDAC resection from 2010 to 2014 were analyzed to determine clinical outcomes of different adjuvant treatment approaches, stratified according to pathologic characteristics. Factors associated with overall survival were identified with multivariable logistic regression and Cox proportional hazards were used to compare overall survival of different treatment approaches in the whole cohort, and propensity score matched groups. Results: We included 16, 709 patients who underwent upfront resection of PDAC. On multivariable analysis, tumor size, grade, positive margin, nodal involvement, lymphovascular invasion (LVI), stage, lymph node ratio, not receiving chemotherapy, and/or radiation were predictors for worse survival. In the presence of at least 1 high-risk pathologic feature (nodal or margin involvement or LVI) chemotherapy with subsequent radiation provided the most significant survival benefit (median survivals: 24.8 vs 21.0 mo for adjuvant chemotherapy; HR = 0.81; 95% CI: 0.77–0.86; P < 0.001 in propensity score matching). The addition of radiation to adjuvant chemotherapy did not significantly improve overall survival in those with no high-risk pathologic features (median survivals: 54.6 vs 42.7 mo for adjuvant chemotherapy; HR=0.90; 95% CI: 0.75–1.08; P = 0.25 in propensity score matching). Conclusions: In the presence of any high-risk pathologic features (nodal or margin involvement or LVI), adjuvant chemotherapy followed by radiation provides a better survival advantage over chemotherapy alone after upfront resection of PDAC. Abstract : Supplemental Digital Content is available in the text